Feasibility of implementing molecular‐guided therapy for the treatment of patients with relapsed or refractory neuroblastoma. (26th February 2015) - Saulnier Sholler, Giselle L.; Bond, Jeffrey P.; Bergendahl, Genevieve; Dutta, Akshita; Dragon, Julie; Neville, Kathleen; Ferguson, William; Roberts, William; Eslin, Don; Kraveka, Jacqueline; Kaplan, Joel; Mitchell, Deanna; et al.
Abstract The primary objective of the study was to evaluate the feasibility and safety of a process which would utilize genome‐wide expression data from tumor biopsies to support individualized treatment decisions. Current treatment options for recurrent neuroblastoma are limited and ineffective, with a survival rate of <10%. Molecular profiling may provide data which will enable the practitioner to select the most appropriate therapeutic option for individual patients, thus improving outcomes. Sixteen patients with neuroblastoma were enrolled of which fourteen were eligible for this study. Feasibility was defined as completion of tumor biopsy, pathological evaluation, RNA quality control, gene expression profiling, bioinformatics analysis, generation of a drug prediction report, molecular tumor board yielding a treatment plan, independent medical monitor review, and treatment initiation within a 21 day period. All eligible biopsies passed histopathology and RNA quality control. Expression profiling by microarray and RNA sequencing were mutually validated. The average time from biopsy to report generation was 5.9 days and from biopsy to initiation of treatment was 12.4 days. No serious adverse events were observed and all adverse events were expected. Clinical benefit was seen in 64% of patients as stabilization of disease for at least one cycle of therapy or partial response. The overall response rate was 7% and the progression free survival was 59 days. This study demonstrates the feasibility and safety of performing real‐time genomic profiling to guide treatment decision making for pediatric neuroblastoma patients.